Temporal Changes in Microrna Expression in Blood Leukocytes from Patients with the Acute Respiratory Distress Syndrome. Issue 6 (June 2017) - Narute, Purushottam; Seam, Nitin; Tropea, Margaret; Logun, Carolea; Cai, Rongman; Sun, Junfeng; Shelhamer, James H.; Meduri, Gianfranco U.; Suffredini, Anthony F.
ABSTRACT: Background: MicroRNA (miRNA) control gene transcription by binding to and repressing the translation of messenger RNA (mRNA). Their role in the acute respiratory distress syndrome (ARDS) is undefined. Methods: Blood leukocytes from 51 patients enrolled in a prior randomized trial of corticosteroids for ARDS were analyzed. After screening eight patients with microarrays for altered miRNA expression, 25 miRNAs were selected for further analysis using RT-PCR in all 51 patients. Results: On day 0, the 51 patients had APACHE III score of 60.4 ± 17.7 and PaO2 /FiO2 of 117 ± 49. 21 miRNA were expressed at increased levels in blood leukocytes at the onset of ARDS compared with healthy controls. These miRNA remained elevated at day 3 and increased further by day 7 (log2 fold change from 0.66 to 5.7 fold, P <0.05 compared to day 0). In a subgroup analysis (37 patients treated with corticosteroids and 14 treated with placebo), the interaction of miRNA expression over time and steroid administration was not significant suggesting that systemic corticosteroids had no effect on the miRNA detected in our study. In contrast, corticosteroids but not placebo decreased IL-6 and C-reactive protein at day 3 ( P < 0.001) demonstrating an early systemic anti-inflammatory response whereas both treatment arms had decreased values by day 7 ( P <0.001). Conclusions: Expression of miRNA is increased in blood leukocytes of patients with ARDS at day 0 and day 3 and rises further by day 7, when systemic inflammation is subsiding. These effects appear independent of the administration of steroids, suggesting different inflammatory modifying roles for each in the resolving phases of ARDS. Abstract : Supplemental Digital Content is available in the text